2012
DOI: 10.1088/0256-307x/29/2/027302
|View full text |Cite
|
Sign up to set email alerts
|

Alternating-Current Transport Properties of the Interface between Nd0.7Sr0.3MnO3Ceramic and a Ag Electrode

Abstract: Electrical transport properties of the interface between a Nd0.7Sr0.3MnO3 ceramic and a Ag electrode are investigated using the ac impedance over a wide temperature and frequency ranges. The ac impedance measurements give the compressed semicircle arcs at different temperatures, which are used for the analysis of different contributions to electrical transport based on an electrical equivalent circuit. A significant interface-dependent electroresistance effect of 530% is clearly developed around the metal-insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…1 under the same measuring condition are also given, as shown in figure 4. The resistivity peak at T MI corresponds to a transition between a ferromagnetic metallic state and a paramagnetic isolating state [24]. For No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 under the same measuring condition are also given, as shown in figure 4. The resistivity peak at T MI corresponds to a transition between a ferromagnetic metallic state and a paramagnetic isolating state [24]. For No.…”
Section: Resultsmentioning
confidence: 99%
“…Besides these factors mentioned above, it is also reported that the microstructure defects, grain/phase boundaries, and various inhomogeneous factors are closely related to the transport properties of manganites due to the resistivity is the structure-sensitive parameters [10], and can induce various novel effects as interface-dependent ER effect, MR effect [11,12], EPIR effect [13][14][15] and low field magnetoresistance (LFMR) effect [16,17]. * Author for correspondence (cpyang@hubu.edu.cn) For the NdSrMnO system with doping ratio x = 0.3, Nd 0.7 Sr 0.3 MnO y generally exhibits an optimal double exchange interaction (DE) accompanied with the Curie temperatures of 229-239 K, and the electromagnetic transport is comprehensively investigated [18][19][20][21][22][23][24]. In this work, an unusual electrical transport behaviour is observed in the NSMO ceramics prepared by solid-state reaction and sequentially thermal-pressure treatment.…”
Section: Introductionmentioning
confidence: 99%